2017
DOI: 10.1104/pp.16.01493
|View full text |Cite
|
Sign up to set email alerts
|

A Salivary Endo-β-1,4-Glucanase Acts as an Effector That Enables the Brown Planthopper to Feed on Rice

Abstract: ORCID IDs: 0000-0002-5714-7586 (J.Z.); 0000-0002-3262-6134 (Y.L.).The brown planthopper (BPH) Nilaparvata lugens is one of the most destructive insect pests on rice (Oryza sativa) in Asia. After landing on plants, BPH rapidly accesses plant phloem and sucks the phloem sap through unknown mechanisms. We discovered a salivary endo-b-1,4-glucanase (NlEG1) that has endoglucanase activity with a maximal activity at pH 6 at 37°C and is secreted into rice plants by BPH. NlEG1 is highly expressed in the salivary gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 57 publications
5
107
0
Order By: Relevance
“…Two secretary proteins that actively participate in salivary sheath formation were recently identified in BPHs (Huang et al, 2015. Furthermore, several salivary proteins that play important roles in interactions between BPH and rice were identified (Petrova and Smith, 2014;Ji et al, 2017;Ye et al, 2017). However, the functions of the majority of BPH-secreted proteins have not yet been experimentally determined.…”
mentioning
confidence: 99%
“…Two secretary proteins that actively participate in salivary sheath formation were recently identified in BPHs (Huang et al, 2015. Furthermore, several salivary proteins that play important roles in interactions between BPH and rice were identified (Petrova and Smith, 2014;Ji et al, 2017;Ye et al, 2017). However, the functions of the majority of BPH-secreted proteins have not yet been experimentally determined.…”
mentioning
confidence: 99%
“…To investigate the effect of DNase II on the H 2 O 2 defence response of wounded plants, purified GFP and DNase II–GFP were applied to wounded rice plants as previously described (Ji et al ., ; Ye et al ., ). We found that the H 2 O 2 level in wounding plus GFP (14.6–15.4 nmol g −1 ) and wounding plus DNase II–GFP (14.3–17.6 nmol g −1 ) significantly increased when compared with the untreated control (8.2–10.6 nmol g −1 ) (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The bioactive components in herbivore saliva have been extensively investigated. For example, calcium‐binding proteins regulate the concentration of free ionic calcium (Will et al ., ); glucanases degrade celluloses in plant cell walls (Ji et al ., ); oxidoreductases detoxify secondary metabolic products and maintain ROS levels in plant tissues (Morgan et al ., ). Here, we reveal that the planthopper saliva can degrade DNA, and that the responsible enzyme is DNase II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present data show that some BPH salivary proteins function as effectors. These include an endo‐ β ‐1,4‐glucanase, salivary DNase II and salivary EF‐hand calcium‐binding protein, which all inhibit the rice defense response to planthoppers. Conversely, some salivary proteins function as elicitors, such as the BPH‐secreted mucin‐like protein, which induces rice defense response against planthoppers.…”
Section: Salivary Proteins Of Bph Function In the Resistance Of Rice mentioning
confidence: 99%